Surgical outcomes of minimally invasive vitrectomy surgery in Eales’ disease - Khanduja, S; Gupta, S; Sinha, S; Venkatesh, Pradeep; Vohra, R; Garg, S (Nepalese Journal of Ophthalmology, 2013)
Introduction: The results of surgical outcomes of 20 gauge pars plana vitrectomy in Eales’ disease are available in the scientific literature. However, all these studies have been done using the 20 gauge vitrectomy systems and most studies have been conducted in a retrospective manner. Objective: To evaluate the outcomes and safety of 23 gauge vitrectomy in complications of Eales’ disease. Materials and methods: Study design: Consecutive interventional case series. Participants: Seventy-six eyes of 72 nonconsecutive patients undergoing 23-gauge vitrectomy for complications of Eales’ disease were enrolled. The participants were followed up for a minimum of one year. Intervention: The participants underwent a complete demographic, medical and ophthalmic evaluation. A 23-gauge vitrectomy was performed. Endotamponade was used when necessary. Perioperative and postoperative events were recorded. Primary outcome measures were visual acuity and complications arising due to surgery. Results: Indication for surgery was non-clearing vitreous hemorrhage in 89.4% (68/76) and secondary retinal detachment in 10.6% (8). Visual acuity improved from Log Mar 1.80 ± 0.19 units preoperatively to Log Mar 0.47±0.59. Best-corrected visual acuity equivalent to Snellen 6/9 was achieved in 77. 6% of eyes. . Surgical failure was seen in 6.5% cases. Four cases were lost due to progression to neovascular glaucoma and 1 case was lost to severe residual retinal detachment. Iatrogenic portside retinal breaks occurred in 3.9% (3), post-vitrectomy retinal detachment 2.6% ( 2), hypotony 1.3% (1) and cataract in 38.1% (28) cases. Conclusion: 23-gauge sutureless vitrectomy in patients with Eales’ disease is a safe and effective technique with acceptable level of risk and complications. Nepal J Ophthalmol 2013; 5(10): 182-189 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8710